2018
DOI: 10.3390/ijms19082429
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Er:YAG and Diode Laser Irradiation on Dental Pulp Cells and Tissues

Abstract: Vital pulp therapy (VPT) is to preserve the nerve and maintain healthy dental pulp tissue. Laser irradiation (LI) is beneficial for VPT. Understanding how LI affects dental pulp cells and tissues is necessary to elucidate the mechanism of reparative dentin and dentin regeneration. Here, we show how Er:YAG-LI and diode-LI modulated cell proliferation, apoptosis, gene expression, protease activation, and mineralization induction in dental pulp cells and tissues using cell culture, immunohistochemical, genetic, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 65 publications
1
16
0
Order By: Relevance
“…Similar results were obtained using different laser types in other studies [ 17 , 18 ]. LLLT application on the pulp–dentine interface after conservative cavity preparation without pulp exposure leads to more aggregated organized collagen fibrils and odontoblast process [ 19 ].…”
Section: Introductionsupporting
confidence: 91%
“…Similar results were obtained using different laser types in other studies [ 17 , 18 ]. LLLT application on the pulp–dentine interface after conservative cavity preparation without pulp exposure leads to more aggregated organized collagen fibrils and odontoblast process [ 19 ].…”
Section: Introductionsupporting
confidence: 91%
“…Kinds of laser have been applied for direct pulp capping therapy in vitro and in vivo . Yamakawa showed that Er:YAG and diode laser irradiation could promote cell proliferation, induce dentin proteins genes expression, and stimulate pulp cell differentiation into functional odontoblasts by activating TGF‐β cell signal pathway (14). Animal experiments showed that the CO 2 laser aid procedures not only enhancing the success rate of vital pulp preservation, but also improving the thickness of reparative dentin bridges (15).…”
Section: Discussionmentioning
confidence: 99%
“…But, inadequate or excessive irradiation can also cause injury. Er:YAG laser may induce cell shrinkage or even apoptosis (14). When lasers are set at high output power, the accumulated heat can cause pulpal damage.…”
Section: Discussionmentioning
confidence: 99%
“…Since pigs are relatively close to humans physiologically and anatomically, they are expected to be used as a model for future regenerative medicine. We previously established the PPU7 cell line from porcine dental pulp cells [ 26 ] and used it for dentin-regeneration research [ 27 , 28 ]. Hence, we used PPU7 cells for basic research to investigate the cell dynamics on the MTA disk.…”
Section: Appendix A1 Fluorescence Microscope Observation Of Dered-pmentioning
confidence: 99%
“…The immortalized porcine dental pulp cell line (PPU7) was established [ 26 ] and has been used for endodontic research associated with laser irradiation [ 27 ]. PPU7 cells can express alkaline phosphatase (ALP) and odontoblastic marker genes that form precipitated nodules when cultured in a medium containing β-glycerophosphate and ascorbic acid.…”
Section: Introductionmentioning
confidence: 99%